Localized juvenile spongiotic gingival hyperplasia possibly originates from the junctional gingival epithelium—an immunohistochemical study. Issue 4 (20th August 2015) - Allon, Irit; Lammert, Kaila M; Iwase, Rei; Spears, Robert; Wright, John M; Naidu, Aparna
Abstract : Aims: To immunohistochemically evaluate the cytokeratin (CK) pattern of expression in localized juvenile spongiotic gingival hyperplasia (LJSGH) as compared with the gingival epithelium (GE). Methods and results: Ten cases of LJSGH were semiquantitatively evaluated for the immunohistochemical pattern of CK1/10, CK4, CK8/18, and CK19. GE controls were taken from 10 cases of reactive gingival fibroepithelial hyperplasia. GEs showed mean positivity rates of 80% for both CK1/10 and CK4, and 5% for both CK8/18 and CK19. LJSGHs showed mean positivity rates of 65% for CK19, 60% for CK8/18, 30% for CK4, and 5% for CK1/10. The differences between LJSGHs and GEs were statistically significant ( P < 0.01). Conclusions: The LJSGH pattern of CK expression is reminiscent of the profile described in the literature for the junctional epithelium (JE). Possibly, JE exteriorized from the gingival sulcus would be more prone to irritation from a variety of sources, resulting in inflammation and hyperplasia, with the subsequent development of LJSGH.